Measuring height of high-voltage transmission poles using unmanned aerial vehicle (UAV) imagery - Qayyum A.; Malik A.S.; Saad N.M.; bin Abdullah M.F.; Iqbal M.; Rasheed W.; Bin Ab Abdullah A.R.; Hj Jaafar M.Y. (Taylor and Francis Ltd., 2023)
Aerial photography; Classification (of information); Cost effectiveness; Electric power transmission; Graphic methods; Object detection; Poles; Remote sensing; Stereo image processing; Vehicle transmissions; Depth Map; Disparity map; Global information systems; Graph cut; High voltage transmissions; Ortho-rectification; Remote sensing applications; Stereo matching algorithm; Unmanned aerial vehicles (UAV)